Physiopathology of necrobiotic xanthogranuloma with monoclonal gammopathy. (10th February 2014) - Szalat, R.; Pirault, J.; Fermand, J.‐P.; Carrié, A.; Saint‐Charles, F.; Olivier, M.; Robillard, P.; Frisdal, E.; Villard, E. F.; Cathébras, P.; Bruckert, E.; Chapman, M. John; et al.
Abstract Rationale Xanthomatosis associated with monoclonal gammopathy includes hyperlipidaemic xanthoma (HX), normolipidaemic xanthoma (NX) and necrobiotic xanthogranuloma (NXG). All three pathologies are characterized by skin or visceral lesions related to cholesterol accumulation, monoclonal immunoglobulin (MIg) and hypocomplementemia. The pathophysiology underlying NXG remains unknown although the involvement of MIg is suspected. Objective To provide further insights into the pathophysiology of NXG, we evaluated the plasma lipid phenotype, mechanisms involved in cellular cholesterol accumulation and role of MIg in an analysis of blood and plasma markers of inflammation in 16 patients with xanthomatosis [NXG (n = 8) and NX (n = 8)] associated with monoclonal IgG relative to the relevant controls. Results The lipid profile of patients with NXG was characterized by a low HDL‐C phenotype and an abnormal distribution of HDL particles. Sera from patients with NXG induced cholesterol accumulation in human macrophages. This accumulation was due in part to a significant reduction in the HDL capacity to promote cholesterol efflux from macrophages, which was not found in the case of NX. The MIg of NXG and NX patients was tested positively by ELISA to recognize a large spectrum of lipoproteins. High plasma levels of pro‐inflammatory cytokines (TNFα and IL‐6), soluble cytokine receptors (sIL‐6R, sTNFRI and sTNFRII), adhesion molecules (VCAM‐1 and ICAM‐1) and chemokines (MCP‐1, IL‐8 and MIP‐1α) were observed in both patients with NXG and NX, revealing a specific xanthoma inflammatory signature which was inversely correlated with plasma levels of anti‐inflammatory HDL. However, patients with NXG were distinguished by elevated levels of IL‐15 and a marked increase in the rate of intermediate CD14++CD16+ monocytes. Conclusion This study revealed that NXG is characterized by impaired macrophage lipid homeostasis associated with a systemic inflammatory profile that may result from the interaction of MIg and lipoproteins.